Love, Kurt the Vonnegut love letters, 1941-1945 - Vonnegut, Kurt 1922-2007 (Random House, 2020)
""If ever I do write anything of length--good or bad--it will be written with you in mind." Kurt Vonnegut's oldest daughter, Edith, was cleaning out her mother's attic when she stumbled upon a dusty box. Inside were more than two-hundred love letters written by Kurt to Jane, spanning the early years of their relationship: from 1941, when nineteen-year-old Kurt heads off to college, to his deployment to Europe in 1944 and the couple's marriage in 1945. The letters are full of the humor and wit that we have come to associate with Kurt Vonnegut. But they also show more private corners of his mind: Passionate and tender, the letters form an illuminating portrait of a young soldier's life in World War II as he attempts to come to grips with love and mortality. And they expose the origins of Vonnegut the writer, when Jane was the only person who believed in him, and they had no idea how celebrated he would become. A beautiful full-color collection of handwritten letters, notes, sketches, and comics, interspersed with Edith's insights and family memories, Love, Kurt is an intimate record of a young man growing into himself, a fascinating account of a writer finding his voice, and a moving testament to the life-altering experience of falling in love"--
Keywords: Vonnegut, Kurt -- 1922-2007; Geschichte 1941-1945; Zweiter Weltkrieg; Vonnegut, Kurt / Correspondence; Letters; Love-letters; LITERARY COLLECTIONS / Letters; BIOGRAPHY & AUTOBIOGRAPHY / Literary Figures; LITERARY COLLECTIONS / American / General; Vonnegut, Kurt; Love letters; Illustrated works; Personal correspondence; Bildband; Briefsammlung